Genetic determinism of cortisol levels in pig - Terenina, Elena; Iannuccelli, Nathalie; Billon, Yvon; Fève, Katia; Gress, Laure; Bazovkina, Darya; Mormede, Pierre; Larzul, Catherine (Frontiers in Genetics, 2025)
In facing the challenge of sustainability, animal breeding provides the option to improve animal robustness. In the search for new selection criteria related to robustness, the hypothalamic–pituitary–adrenocortical (HPA) axis is studied as a major neuroendocrine system involved in metabolic regulations and adaptive responses. Indeed, HPA axis activity is strongly influenced by genetic factors acting at several levels of the axis. The adrenocorticotropic hormone (ACTH) stimulation test has long been used to analyze interindividual and genetic differences in HPA axis activity in several species, including pigs. To uncover the genetic determinism of HPA activity and its influence on functional traits and robustness, a divergent selection experiment was carried out for three generations in a Large White pig population based on plasma cortisol levels measured one hour after injection of ACTH. In the present study the response to selection was very strong (confirming our previous studies), with a heritability value of cortisol level after ACTH injections reaching 0.64 (±0.03). The difference between the two divergent lines was around five genetic standard deviations after three selection steps. A genome-wide association study pointed out the importance of the glucocorticoid receptor gene (NR3C1) in this response. The measurement of plasma corticosteroid-binding globulin (CBG) binding capacity excluded any significant role of CBG in this selection process. The phenotypic effect of selection on body weight and growth rate was modest and/or inconsistent across generations. The HPA axis, a major neuroendocrine system involved in adaptation processes is highly heritable and responsive to genetic selection. The present experiment confirms the importance of glucocorticoid receptor polymorphism in genetic variation of HPA axis activity–in addition to the previously demonstrated role of CBG gene polymorphism. Further studies will explore the effect of this divergent selection on production and robustness.